Osteocalcin Signaling in Myofibers Is Necessary and Sufficient for Optimum Adaptation to Exercise - Mera, Paula; Laue, Kathrin; Ferron, Mathieu; Confavreux, Cyril; Wei, Jianwen; Galán-Díez, Marta; Lacampagne, Alain; Mitchell, Sarah J.; Mattison, Julie A.; Chen, Yun; Bacchetta, Justine; Szulc, Pawel; et al. (Cell metabolism, 2016)
Circulating levels of undercarboxylated and bioactive osteocalcin double during aerobic exercise at the time levels of insulin decrease. In contrast, circulating levels of osteocalcin plummet early during adulthood in mice, monkeys, and humans of both genders. Exploring these observations revealed that osteocalcin signaling in myofibers is necessary for adaptation to exercise by favoring uptake and catabolism of glucose and fatty acids, the main nutrients of myofibers. Osteocalcin signaling in myofibers also accounts for most of the exercise-induced release of interleukin-6, a myokine that promotes adaptation to exercise in part by driving the generation of bioactive osteocalcin. We further show that exogenous osteocalcin is sufficient to enhance the exercise capacity of young mice and to restore to 15-month-old mice the exercise capacity of 3-month-old mice. This study uncovers a bone-to-muscle feedforward endocrine axis that favors adaptation to exercise and can reverse the age-induced decline in exercise capacity. [Display omitted] •Bone via the hormone osteocalcin improves muscle function during exercise•Circulating osteocalcin levels decrease in aging mice, monkeys, and humans•Osteocalcin promotes muscle uptake and utilization of glucose and fatty acids•Osteocalcin promotes muscle IL-6 secretion during exercise Mera et al. show that the bone-derived hormone osteocalcin is necessary for optimum exercise capacity and that this hormone decreases with aging in mice, monkeys, and humans of both genders. Osteocalcin promotes muscle uptake and utilization of glucose and lipids during exercise and greatly improves the exercise capacity of old mice.